Essay writing for english tests: New edition-extensively revised - Duigu, Gabi (Nxb. Tp. Hồ Chí Minh, 2003)
This book contains -120 Writing Topics -120 Model Essays -120 Essay Outlines -1200 Model Sentences Great for -ESL Learners -High School Students -Test Prep Students -College Students *This book is a sequel to 120 Writing Topics. It only contains 120 writing topics and sample essays